Decision Support System for Determining the Best Homeroom Teacher at SMA Negeri 1 Perbaungan Using the Simple Additive Weighting Method - Wira Apriani (Jurnal ICT : Information and Communication Technologies, 2022)
Decision Support System (DSS) is a procedure-based model to process data and assist management in making decisions. Computer-based Decision Support System to improve decision-making ability to solve quasi-structured or unstructured problems. One of the methods that can be used to solve problems in this DSS is the Simple Additive Weighting (SAW) method. The SAW method is a method that uses weighted addition. With this method the optimal solution is sought from a number of alternatives and certain criteria. This application is desktop-based so that it can be used by users and aims to make it easier for users to need information and solutions to help choose the best homeroom teacher